The Applicability of Item Response Theory Based Statistics to Detect Differential Item Functioning in Polytomous Tests - Abdul Wahab Ibrahim (Randwick International of Education and Linguistics Science Journal, 2020)
The study used statistical procedures based on Item Response Theory to detect Differential Item Functioning (DIF) in polytomous tests. These were with a view to improving the quality of test items construction. The sample consisted of an intact class of 513 Part 3 undergraduate students who registered for the course EDU 304: Tests and Measurement at Sule Lamido University during 2017/2018 Second Semester. A self-developed polytomous research instrument was used to collect data. Data collected were analysed using Generalized Mantel Haenszel, Simultaneous Item Bias Test, and Logistic Discriminant Function Analysis. The results showed that there was no significant relationship between the proportions of test items that function differentially in the polytomous test when the different statistical methods are used. Further, the three parametric and non-parametric methods complement each other in their ability to detect DIF in the polytomous test format as all of them have capacity to detect DIF but perform differently. The study concluded that there was a high degree of correspondence between the three procedures in their ability to detect DIF in polytomous tests. It was recommended that test experts and developers should consider using procedure based on Item Response Theory in DIF detection.